2014 Innovative Applications of Computational Intelligence on Power, Energy and Controls With Their Impact on Humanity (CIPECH) 2014
DOI: 10.1109/cipech.2014.7019049
|View full text |Cite
|
Sign up to set email alerts
|

A 180 nm low power CMOS operational amplifier

Abstract: The desired specifications of the design are given in the Table I below.Generic block diagram of simple two-stage op amp is shown in figure 1 below. First stage consists of high-gain differential amplifier. Mostly cascading is used to enhance the gain in this stage. This stage has the most dominant pole of the system. A common source single stage amplifier is usually used as a second stage, which gives high output voltage swing. Third stage is most commonly implemented as the unity-gain source follower circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Finally, a comparison work is tabulated among various techniques for designing the comparator, which is shown in Table 1. 475 From Figure 6 it is shown that this comparator circuit achieved lower power dissipation, which is only 2.84 µW under supply voltage 1.2 V. In this research works, the lower power dissipation is obtained by maintaing the proper transistor sizing and small capacitnace values, which helps to dissipates lower power than [12]. From Table 1, it is shown that the output gain and gain bandwidth of this research is found lower compared to [15].…”
Section: Results and Analysismentioning
confidence: 69%
See 2 more Smart Citations
“…Finally, a comparison work is tabulated among various techniques for designing the comparator, which is shown in Table 1. 475 From Figure 6 it is shown that this comparator circuit achieved lower power dissipation, which is only 2.84 µW under supply voltage 1.2 V. In this research works, the lower power dissipation is obtained by maintaing the proper transistor sizing and small capacitnace values, which helps to dissipates lower power than [12]. From Table 1, it is shown that the output gain and gain bandwidth of this research is found lower compared to [15].…”
Section: Results and Analysismentioning
confidence: 69%
“…4, December 2018: 471 -476 472 stage amplifier is often implemented to achieve higher gain as it provides higher output swing in the second stage [9]. It also provides better CMRR, lower power consumption and slew rate [8], [12]. However, it requires frequency compensation for stability in closed loop application where this amplifier has multiple zeros and poles [8], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In paper [4] Ketan. J. Raut represented the design of two-stage op-amp using standard 180nm technology and achieved the parameter.…”
Section: Literature Surveymentioning
confidence: 99%
“…It can be considered as a power efficient and moderate speed op-amp as it achieves a power dissipation of 6.79 μW and a slew rate of 40.56 V/μs. If we compare these results with MOSFET op-amp shown in [41], our TFET-based simulation provides better result in almost every aspect, making it desirable to replace MOSFET in analogue applications in the near future. However, it is also necessary to first build a compact model for TFET to make it more realistic in terms of analogue and digital applications.…”
mentioning
confidence: 96%